A case study on performance management system of a family owned company: presumptions, perceptions and implementation - Abdul Halim, Ayob (2020)
The main purpose of this study was to analyse the presumptions, perceptions and implementation of Performance Management System (PMS) in a private family owned company. This study examined the presumptions, perceptions and the responses of the upper level management and the lower level management of ABC company on the implementation of PMS. A total of 10 respondents were interviewed extensively and qualitatively to extract the results of the study. The findings in this study showed that the upper level management generally provide a globalized outlook of the system and how it can be implemented to grow the organisation. In spite of that, there are several upper level management personnel who did not have clear perceptions and presumptions of what PMS is for the company. In contrary, the lower level management provide a grounded outlook, a day-to-day notion of the system and how it can be implemented, specifying on going office administrative situation in ABC company. Due to the non-existence of PMS, there are several key issues that have been the stumble blocks for the development of ABC company. There are several positive notions on its implementation as well as negative notions on it in from the perceptions and presumptions of the respondents. This study sets out to be a reference for start-up family owned company to develop a systematic PMS, considering various familial factors in the Malaysian context and extends the knowledge about PMS in family owned company.